Anti-TNF-α Therapy for Refractory Uveitis Associated with Behçet's Syndrome and Sarcoidosis: A Single Center Study of 131 Patients. (2nd January 2022) - Kunimi, Keiko; Usui, Yoshihiko; Asakage, Masakai; Maehara, Chihiro; Tsubota, Kinya; Mitsuhashi, Ryosuke; Umazume, Akihiko; Kezuka, Takeshi; Sakai, Jun-Ichi; Goto, Hiroshi
ABSTRACT: Purpose: The efficacy of infliximab (IFX) and adalimumab (ADA) for treating Behçet's syndrome (BS) and sarcoidosis has not been compared adequately. Methods: We reviewed the medical records of patients with uveitis diagnosed at Tokyo Medical University Hospital and compared the efficacy of IFX and ADA for BS and the efficacy of ADA for sarcoidosis and BS. Results: 68 patients in IFX group and 63 patients in ADA group were analyzed. In BS patients, IFX and ADA were both effective in improving uveitic macular edema (UME). ADA improved UME in BS but not in sarcoidosis patients. The efficacy of ADA in reducing doses of corticosteroids and glaucoma medications was better in sarcoidosis than in the BS group. Conclusion: Both IFX and ADA are efficacious in improving UME in BS patients. The reason that ADA improves UME better in BS than in sarcoidosis may be due to the difference in pathogenesis between these diseases.